Demystifying the Impact of Marketing Decisions on Market Share and Firm Value - A Chain-of-effects Perspective - Adithipyangkul, pattarin; Sharma, Piyush; Leung, Tak Yan (2020)
This paper uses the ‘chain-of-effects’ framework for marketing productivity and agency theory to explore the underlying mechanism that drives the effects of marketing decisions (measured by marketing expenses and relative compensation for executive directors with marketing experience) on firm value (Tobin’s Q) via firm performance (market share). Data from 491 Chinese listed companies over the 2010-14 period shows that marketing expenditure positively affects firm value but not through market share. In contrast, relative compensation positively affects firm value, both directly and through market share. Moreover, the positive effect of relative compensation on market share appears to be stronger in an organization with more severe agency conflicts. Besides extending current research on the effects of marketing decisions on financial outcomes, these results highlight the importance of having executive directors with marketing experience to increase firm value.